1998
DOI: 10.1038/sj.onc.1201584
|View full text |Cite
|
Sign up to set email alerts
|

Growth-dependent and PKC-mediated translational regulation of the upstream stimulating factor-2 (USF2) mRNA in hematopoietic cells

Abstract: Upstream stimulating factor (USF2) is a basic helix ± loop ± helix leucine zipper transcription factor, which is found in most tissues. A critical role for USF2 in cellular proliferation has been proposed based on its importance in the regulation of various cyclins and P53 and its capability to antagonize c-myc. In this paper we report that IL-3, which is a major growth factor for mast cells, induces USF2 protein synthesis in murine mast cells . Surprisingly, it does not signi®cantly a ect the level of USF2 mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…In addition, IL-3 was reported to induce USF2 protein synthesis in murine mast cells [45]. Moreover, by crosslinking of Fc 4 RI, c-Fos protein was shown to be produced.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IL-3 was reported to induce USF2 protein synthesis in murine mast cells [45]. Moreover, by crosslinking of Fc 4 RI, c-Fos protein was shown to be produced.…”
Section: Discussionmentioning
confidence: 99%
“…In nontumorigenic mammary epithelial cells, USF2 regulates the transcript levels of insulin-like growth factor 2 receptor, but interestingly it loses its ability to transactivate insulin-like growth factor 2 receptor in breast cancer cells (38). Furthermore, extensive studies were carried out on the regulation of USF2 expression in interleukin 3 activated mast cells, where an induction of USF2 protein synthesis was observed via increased translational efficiency (22,48). We previously utilized cell permeable peptides as inhibitors of the activity of the USF2 proteins, to demonstrate its possible role in mast cell survival (9).…”
Section: Discussionmentioning
confidence: 99%
“…Initially we demonstrated decreased expression of USF2 as a result of antisense oligonucleotide inhibition of PKC in FcεRI-stimulated mast cells [16]. We also showed that IL-3 induced USF2 protein synthesis in mast cells [17]. However, it did not significantly affect the level of USF2-mRNA in these cells.…”
Section: Introductionmentioning
confidence: 99%
“…Using polysomal fractionation techniques and RNA analysis, we demonstrated that this translational regulation is mostly the result of increased USF2 translational efficiency [17]. Additionally, PKC inhibitors (calphostin C and long-term exposure to PMA) prevented both the induction of USF2 protein synthesis and the increase in USF2 translational efficiency in IL-3-activated mast cells, showing that PKC is involved in mediating the translational response of USF2 [17]. This observation is intriguing since only few studies have studied the role of PKC in translational regulation.…”
Section: Introductionmentioning
confidence: 99%